2020
DOI: 10.1111/jcmm.15559
|View full text |Cite
|
Sign up to set email alerts
|

Role of CARD9 in inflammatory signal pathway of peritoneal macrophages in severe acute pancreatitis

Abstract: Previous studies revealed that caspase recruitment domain protein 9 (CARD9) was involved in severe acute pancreatitis (SAP) inflammation and that interfering with its expression in vivo could inhibit inflammation. However, the specific mechanism is unknown. This study aimed to discover the related signal pathways of CARD9 in macrophages. SiRNA interference technology was used in vivo and in vitro to detect CARD9‐related signal pathways in peritoneal macrophages. Furthermore, Toll‐like receptor 4 (TLR4) and mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…It has been studied that SYK can active Card9-NF-κB signaling and activating PAD4-NETs signaling through SYK-dependent reactive oxygen species production ( 25 , 31 ). NF-κB plays a crucial role in transcriptional activation of many proinflammatory genes, including the genes of cytokines and chemokines ( 25 , 49 , 50 ). NETs itself could cause inflammation, as well as through promoting a proinflammatory subtype transition of microglia or macrophage ( 17 , 19 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been studied that SYK can active Card9-NF-κB signaling and activating PAD4-NETs signaling through SYK-dependent reactive oxygen species production ( 25 , 31 ). NF-κB plays a crucial role in transcriptional activation of many proinflammatory genes, including the genes of cytokines and chemokines ( 25 , 49 , 50 ). NETs itself could cause inflammation, as well as through promoting a proinflammatory subtype transition of microglia or macrophage ( 17 , 19 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…MyD88 activation and CARD9-mediated IFN-γ production are critically involved in preventing the infection of coccidioides in mice ( 61 ). Deletion of CARD9 with siRNA inhibits the signaling from TLR4 and Dectin‐1 in macrophages and reduces the phosphorylation of NF‐κB and p38 MAPKs, leading to decreased production of inflammatory cytokines ( 62 ).…”
Section: Card9 Signaling Is Critical For the Production Of Cytokines/...mentioning
confidence: 99%
“…For example, studies have shown that signaling complexes, comprising of CARD9-BCL10-Malt 1, play critical roles in the activation of NF-κB signaling pathway in C-type lectin receptor (CLR) induced inflammatory responses [ 46 ]. Published evidence also suggests strong connection between over expression of CARD9 in the activation of p38 MAPK during inflammation [ 47 , 48 ]. Lastly, studies by Wang and coworkers have demonstrated that obesity promotes activation of p38MAPK through the upregulation of CARD9-BCL10 complex [ 49 ].…”
Section: Resultsmentioning
confidence: 99%